Cyclic transient behavior of the Joule–Brayton based pumped heat electricity storage: Modeling and analysis. (September 2019) - Wang, Liang; Lin, Xipeng; Chai, Lei; Peng, Long; Yu, Dong; Chen, Haisheng
Abstract: Pumped heat electricity storage (PHES) has the advantages of a high energy density and high efficiency and is especially suitable for large-scale energy storage. The performance of PHES has attracted much attention which has been studied mostly based on steady thermodynamics, whereas the transient characteristic of the real energy storage process of PHES cannot be presented. In this paper, a transient analysis method for the PHES system coupling dynamics, heat transfer, and thermodynamics is proposed. Judging with the round trip efficiency and the stability of delivery power, the energy storage behavior of a 10 MW/4 h PHES system is studied with argon and helium as the working gas. The influencing factors such as the pressure ratio, polytropic efficiency, particle diameters, structure of thermal energy storage reservoirs are also analyzed. The results obtained indicate that, mainly owing to a small resistance loss, helium with a round-trip efficiency of 56.9% has an overwhelming advantage over argon with an efficiency of 39.3%. Furthermore, the increases in the pressure ratio and isentropic efficiencies improve the energy storage performance considerably. There also exit optimal values of the delivery compression ratio, particle sizes, length-to-diameter ratios of the reservoirs, and discharging durations corresponding to the maximum round-trip efficiency and preferable discharging power stability. The above can provide a basis for the optimal design and operation of the Joule–Brayton based PHES. Highlights: The transient analysis method for PTES system is proposed. The cyclic transient of 10 MW/4 h Joule-Brayton PTES is studied. Both the round-trip efficiency and delivery stability of the PTES are discussed. Helium has the overwhelming advantage above argon as the working gas. Impact of particle sizes and length to diameter ratio of packed bed was analyzed.